Cleaning of Lavatory- An Important Task - Aulanko , Marja (Nurture, 2022)
A lavatory is a challenging cleaning object. The space is often rather small, working postures are inconvenient and dirt is disgusting. The aim of this research was to find out what people think about lavatory cleaning. The main focus was on young adults. The material consists of the writing of the first-year university students and students in a home economics school. The material was analysed using content analysis, which showed that in lavatory cleaning there are two different orientations: work order orientation and dirt orientation.